Study on Blood Serum Levels of Heavy and Trace Metals in Chronic Non-Healing Wounds - Dixit R.; Chaudhary N.K.; Mishra P.K.; Srivastava P.; Bhartiya S.K.; Pratap A.; Basu S.; Shukla V.K. (My University, 2025)
Wound healing is a complex, highly regulated process that is important in sustaining the skin barrier function. The etiologic relation of specific metals is not adequately described for chronic non-healing wounds. The aim of this study was to estimate heavy and trace metals in chronic non-healing wound and their association with wound healing. The levels of zinc, selenium, copper, magnesium, chromium, cadmium, iron, and lead were estimated in serum of chronic non-healing wound patients using atomic absorption spectrophotometry. The tests were carried out in 50 patients with chronic non-healing wound and thirty healthy volunteers as control. The serum levels of elements namely zinc, selenium, copper, magnesium, and chromium were significantly reduced in chronic non-healing wounds (P <.001) as compared to control. Lead and cadmium levels had shown the significantly increasing trend in chronic non-healing wound cases (P <.001). The present study demonstrated a significant decrease in serum, levels of selenium, zinc, copper, magnesium, iron, and chromium levels in patients with chronic non-healing wound indicating an association between these elements and wound healing. To summarize the findings of our research, hence trace elements were decreasing in chronic non-healing wound patients suggesting their role in wound healing. © The Author(s) 2022.